(untitled) (KASBIT Business Journal, 2018)
Entrepreneurial intentions have received enormous attention from the research scholars, entrepreneurs, policy makers and practitioners. Entrepreneurial intentions are an evolving area within the field of entrepreneurship and its importance is evident from increasing number of publications and citations even in the top tier journals. Researchers have developed a number of models that evolved with the passage of time and generated new knowledge. But, as the new knowledge emerges, it also raises question that needs to be addressed. There is a need to systematically analyze the stock of studies into consideration. Therefore, aim of the study is to carry out a systematic literature review in order to do citation and thematic analysis. For this purpose, 110 research papers focused on entrepreneurial intentions published between 2005 and 2012 in the renowned electronic databases were considered for analysis. Citation analysis was carried out by the researcher to segregate the main themes emerging from the previous studies. Thematic analysis was also conducted by the researcher for dividing papers into diversified categories and sub-categories. Five main themes along with an additional theme that cannot be easily adjusted to any other theme were recognized. A number of research gaps were identified that can provide fresh new perspectives and future directions for the researchers in the field of entrepreneurship.